HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS IN ADULTS: LOW INCIDENCE OF PRIMARY NEOPLASM AS A TRIGGER IN A CASE SERIES FROM TURKEY - KORTEN, VOLKAN; Arslan, Ferhat (My University, 2018)
This study aimed to investigate the clinical and laboratory features and outcomes of Turkish patients with Hemophagocytic Lymphohistiocytosis. The medical records of 26 HLH adult patients (≥ 16 years of age) were retrospectively analyzed. Gender, age, the duration of fever, time to diagnosis, etiology and laboratory data were extracted from the records. The mean age was 38 ± 18 years, and 15 (58%) patients were female. A total of nine cases had infectious diseases, four cases had rheumatologic diseases, three cases had hematological malignancies while nine cases could not be obtained a definitive diagnosis. The median time to detection of HLH was 20 days (IQR: 8-30 d). Of the 25 patients, 11 (44%) died. The erythrocyte sedimentation rates of the surviving and non-surviving patients were 39 ± 22 mm/h and 15 ± 13 mm/h, respectively. When a long-lasting fever is complicated by bicytopenia or pancytopenia (especially), clinicians must promptly consider the possibility of HLH syndrome to improve patients’ prognosis
HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS IN ADULTS